2015
DOI: 10.1142/s1088424615500856
|View full text |Cite
|
Sign up to set email alerts
|

Metal-free and metal porphyrins: A highly efficient catalysts to Li/SOCl2 battery

Abstract: Two metal-free porphyrins H[Formula: see text]Pp (a, b) and four metalloporphyrins CuPp (a, b) and ZnPp (a, b) have been applied to lithium/thionyl chloride (Li/SOCl[Formula: see text] battery as the high efficient catalysts for the first time. Notably, the battery discharge time in blank is only 1080 s while that of Li/SOCl2 battery after adding porphyrin/metalloporphyrins is 1980 s for H[Formula: see text]Pp (a), 2160 s for H[Formula: see text]Pp (b), 1560 s for CuPp (a), 1320 s for CuPp (b), 1620 s for ZnPp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…The authors have observed localized corrosion in both the Al-rich matrix (where the Cu content is 2 wt% or less) and the interdendritic zones (containing higher Cu content). As previously reported [11,59], the presence of h-phase particles in the interdendritic regions induces galvanic interaction between these particles and the adjacent a(Al) matrix that may lead to localized corrosion. Such intermetallics possesses higher corrosion potential as compared to that of the matrix and acts as a cathode in localized corrosion inducing selective dissolution of the surrounding matrix [57].…”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…The authors have observed localized corrosion in both the Al-rich matrix (where the Cu content is 2 wt% or less) and the interdendritic zones (containing higher Cu content). As previously reported [11,59], the presence of h-phase particles in the interdendritic regions induces galvanic interaction between these particles and the adjacent a(Al) matrix that may lead to localized corrosion. Such intermetallics possesses higher corrosion potential as compared to that of the matrix and acts as a cathode in localized corrosion inducing selective dissolution of the surrounding matrix [57].…”
Section: Resultssupporting
confidence: 56%
“…Oxygen concentration in the matrix areas surrounding h and x particles for the Al-3 wt%Cu-(0.5 wt%Mg) alloys after the corrosion tests can be seen. Birbilis and Buchheit [11] as well as Li and Dang [59] have also reported that x-Al 7 Cu 2 Fe particles sustain relatively large cathodic current densities because of the effect of both Cu and Fe, indicating that it may be an archetypal nobler particle with low dissolution rate and high efficiency for supporting oxygen reduction. Considering the case of the ternary alloy, it has been suggested that the S-Al 2 CuMg phase has not dissolved as unique entity.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Synchronously, research demonstrated that an efficient catalyst system for this cycloaddition reaction usually needs to contain two active sites, Lewis acid and nucleophile 23 . Especially, metalloporphyrins that have been proved to be useful for photocatalytic degradation of organic pollutants, 24 electrocatalysis of redox reaction in batteries 25–27 and oxidation of olefins 28 also show relatively high catalytic activity for cycloaddition of CO 2 with epoxides owing to the presence of metal centers as Lewis acid active sites and the stability, high efficiency, easy to modify and other excellent characteristics of the porphyrin molecules 29,30 . Meanwhile, manganese, magnesium, zinc, cobalt, nickel, aluminum, and other metals have been applied successfully to the cycloaddition of various epoxides and CO 2 31–37 .…”
Section: Introductionmentioning
confidence: 99%